Asc Modulates the Function of NLRC4 in Response to Infection of Macrophages by Legionella pneumophila - Christopher L. Case (American Society for Microbiology, 2011)
ABSTRACT Nucleotide-binding domain, leucine-rich repeat containing proteins (NLRs) activate caspase-1 in response to a variety of bacterium-derived signals in macrophages. NLR-mediated activation of caspase-1 by Legionella pneumophila occurs through both an NLRC4/NAIP5-dependent pathway and a pathway requiring the adapter protein Asc. Both pathways are needed for maximal activation of caspase-1 and for the release of the cytokines interleukin-1β (IL-1β) and IL-18. Asc is not required for caspase-1-dependent pore formation and cell death induced upon infection of macrophages by L. pneumophila. Here, temporal and spatial localization of caspase-1-dependent processes was examined to better define the roles of Asc and NLRC4 during infection. Imaging studies revealed that caspase-1 localized to a single punctate structure in infected cells containing Asc but not in cells lacking this adapter. Both endogenous Asc and ectopically produced NLRC4 tagged with green fluorescent protein (GFP) were found to localize to caspase-1 puncta following L. pneumophila infection, suggesting that NLRC4 and Asc coordinate signaling through this complex during caspase-1 activation. Formation of caspase-1-containing puncta correlated with caspase-1 processing, suggesting a role for the Asc/NLRC4/caspase-1 complex in caspase-1 cleavage. In cells deficient for Asc, NLRC4 did not assemble into discrete puncta, and pyroptosis occurred at an accelerated rate. These data indicate that Asc mediates integration of NLR components into caspase-1 processing platforms and that recruitment of NLR components into an Asc complex can dampen pyroptotic responses. Thus, a negative feedback role of complexes containing Asc may be important for regulating caspase-1-mediated responses during microbial infection. IMPORTANCE Caspase-1 is a protease activated during infection that is central to the regulation of several innate immune pathways. Studies examining the macromolecular complexes containing this protein, known as inflammasomes, have provided insight into the regulation of this protease. This work demonstrates that the intracellular bacterium Legionella pneumophila induces formation of complexes containing caspase-1 by multiple mechanisms and illustrates that an adapter molecule called Asc integrates signals from multiple independent upstream caspase-1 activators in order to assemble a spatially distinct complex in the macrophage. There were caspase-1-associated activities such as cytokine processing and secretion that were controlled by Asc. Importantly, this work uncovered a new role for Asc in dampening a caspase-1-dependent cell death pathway called pyroptosis. These findings suggest that Asc plays a central role in controlling a distinct subset of caspase-1-dependent activities by both assembling complexes that are important for cytokine processing and suppressing processes that mediate pyroptosis.